Quinolinium single crystals with a high optical nonlinearity and unusual out-of-plane polar axis. Issue 47 (28th November 2017) - Choi, Jae-Young; Lee, Seung-Jun; Lee, Seung-Chul; Jeong, Chan-Uk; Jazbinsek, Mojca; Yun, Hoseop; Kang, Bong Joo; Rotermund, Fabian; Kwon, O-Pil
Abstract : New phenolic quinolinium crystals with very large macroscopic optical nonlinearity and good crystal-growth ability exhibit an out-of-plane polar axis, which is very unusual considering other state-of-the-art organic nonlinear optical crystals exhibiting an in-plane polar axis. Abstract : New highly efficient nonlinear optical crystals based on phenolic quinolinium with various benzenesulfonate and thiophenesulfonate anions are reported for photonic applications. All phenolic quinolinium crystals exhibit strong second harmonic generation (SHG) efficiency. Among them, OHQ-MBS crystals (2-(4-hydroxystyryl)-1-methylquinolinium 4-methoxybenzenesulfonate) with acentric monoclinic Pn space group symmetry exhibit very large macroscopic second-order optical nonlinearity with diagonal effective hyperpolarizability of about 120 × 10 −30 esu, which is comparable to the state-of-the-art organic nonlinear optical crystals. OHQ-MBS single crystals with a large area of over 5 × 5 mm 2 and good optical quality were successfully grown using a solution growth method in mixed solvent systems. Interestingly, as-grown OHQ-MBS single crystals exhibit an out-of-plane polar axis, which is very unusual, because the state-of-the-art organic nonlinear optical as-grown crystals commonly exhibit an in-plane polar axis. The out-of-plane polar axis is very beneficial for applying various optical configurations. In addition, OHQ-MBS single crystals with an in-plane polar axis are also successfully prepared using a simple cleaving method. Therefore, OHQ-MBS crystals with easily accessible both out-of-plane and in-plane polar axes, as well as the state-of-the-art optical nonlinearity may open up a range of new possibilities for photonic applications.